THEMATIC STUDY: HARAPAN DALAM BERDOA (AL-ṬAMA’) DAN IMPLEMENTASINYA DI ERA MODERN PERSEKTIF Q. SHIHAB DAN W. AL-ZUḤAILĪ - Zyan Anggra Ulfia Nasution; Abdul Halim; Hery Syahputra (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This research addresses the reliance of the Muslim community on social media influencers, which contradicts Islamic teachings that emphasize hoping only in Allah. A qualitative approach is used, with primary data from Qur’anic verses on al-Ṭama’ in Tafsir Al-Misbah and Al-Munir, and secondary data from relevant literature. The study descriptively analyzes the thematic concept of al-Ṭama’ in prayer, highlighting sincere and exclusive hope in Allah. The findings reveal that the Qur’anic concept of al-Ṭama’ balances hope and fear (khauf) in worship, emphasizing prayer as vertical communication with Allah to increase faith and closeness to Him. Implementation in the Muslim community involves belief in Allah, submission, consistency, right intention, and steadfastness in prayer.